Switched control via static output feedback for uncertain LTI systems - Vargas, Leandro Campos (2023)
The switched static output feedback control applied to uncertain linear time-invariant (LTI) systems is addressed in this work.The approach chosen for the design of static output feedback (SOF) gains is based on the two-stage method, which consists in obtaining a state feedback gain matrix which is then used as an input parameter for the design of the desired static output feedback gain at the second stage. The solution for the investigated problems is presented in terms of linear matrix inequalities (LMIs), obtained by means of the application of the Finsler’s Lemma. The method proposed was applied on the design of controllers for an active suspension system. In the practical experiments the dynamic performance achieved with the implementation of the derived controllers attests to the potential of the proposed strategy for designing switched static output feedback controllers. The obtained results are compared with a robust static output feedback controller design.